(untitled) (International Journal of Engineering and Computer Science, 2015)
Steganography is a tool for hiding information inside an image. It usually deals with different approaches of hiding the existence of the communicated data or message in a way that it remains confidential. It maintains integrity of message between two communicating bodies. In image steganography, message image is hidden in cover image and a stego-image is generated. There are different types of steganography techniques having pros and cons. In this paper, we review the various data hiding techniques that are used to implement a steganography such as LSB, ISB, MLSB etc.